Muons, mutations, and planetary shielding - de Groen, Piet C. (Frontiers in Astronomy and Space Sciences, 2022)
Life on earth is protected from astrophysical cosmic rays by the heliospheric and slowly varying magnetospheric magnetic fields, and by collisions with oxygen and nitrogen molecules in the atmosphere. The collisions generate showers of particles of lesser energy; only muons, a charged particle with a mass between that of an electron and a proton, can reach earth’s surface in substantial quantities. Muons are easily detected, used to image interior spaces of pyramids, and known to limit the stability of qubits in quantum computing; yet, despite their charge, average energy of 4 GeV and ionizing properties, muons are not considered to affect chemical reactions or biology. In this Perspective the potential damaging effects of muons on DNA, and hence the repercussions for evolution and disease, are examined. It is argued here that the effect of muons on life through DNA mutations should be considered when investigating the protection provided by the magnetic environment and atmosphere from cosmic rays on earth and exoplanets.